How Can Termites Achieve Their Unparalleled Postembryonic Developmental Plasticity? A Test for the Role of Intermolt-Specific High Juvenile Hormone Titers - Korb, Judith; Greiner, Carolin; Foget, Marion; Geiler, Adrian (Frontiers in Ecology and Evolution, 2021)
Termites are ‘social cockroaches’ and amongst the most phenotypically plastic insects. The different castes (i.e. two types of reproductives, workers and soldiers) within termite societies are all encoded by a single genome and present the result of differential postembryonic development. Besides the default progressive development into winged sexuals of solitary hemimetabolous insects, termites have two postembryonic, non-terminal molts (stationary and regressive; i.e., molts associated, respectively, with no change or reduction of size/morphological differentiation) which allow them to retain workers, and two terminal developmental types to become soldiers and replacement reproductives. Despite this unique plasticity, especially the mechanisms underlying the non-terminal development are poorly understood. In 1982, Nijhout and Wheeler proposed a model how this diversity might have evolved. They proposed that varying juvenile hormone (JH) titers at the start, mid-phase, and end of each intermolt period account for this developmental diversity. We tested this rarely addressed model in the lower termite Cryptotermes secundus using phase-specific pharmacological manipulations of JH titers. Our results partially support this model. These data are supplemented with gene expression studies of JH related genes that characterize different postembryonic developmental trajectories. Our study provides new insights into the evolution of the unique postembryonic developmental plasticity of termites that constitutes the foundation of their social life.